2023
DOI: 10.1111/bjh.18704
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of human immunodeficiency virus‐associated Burkitt lymphoma and diffuse large B‐cell lymphoma treated in Australia: A report from the Australasian Lymphoma Alliance

Abstract: People living with human immunodeficiency virus (HIV) (PLWH) have an increased risk of developing non-Hodgkin lymphoma (NHL). 1 The two subtypes of NHL most commonly seen in PLWH are diffuse large B-cell lymphoma (DLBCL) and Burkitt lymphoma (BL). Other subtypes include primary central nervous system (CNS) lymphoma, primary effusion lymphoma and plasmablastic lymphoma. Historically, prior to the introduction of antiretroviral therapy (ART), HIV-associated lymphomas conferred a poor prognosis, with a 10% 2-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…According to research by Lim et al, patients with HIV-DLBCL had a 2-year PFS of 77% and an OS of 81%, while those with HIV-BL had a 2-year PFS of 67% and an OS of 67% [13] , Coutinho et al showed a 5-year OS of 78% versus 64% in HIV-positive and HIV-negative DLBCL respectively [29] , in patients with HIV-DLBCL, Besson et al reported a 2-year PFS and OS of 75% and 75%, respectively [28] . Regardless of HIV status, a US retrospective research for HIV-BL reported a 3-year PFS and OS rate of 64% and 70%, respectively [30] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to research by Lim et al, patients with HIV-DLBCL had a 2-year PFS of 77% and an OS of 81%, while those with HIV-BL had a 2-year PFS of 67% and an OS of 67% [13] , Coutinho et al showed a 5-year OS of 78% versus 64% in HIV-positive and HIV-negative DLBCL respectively [29] , in patients with HIV-DLBCL, Besson et al reported a 2-year PFS and OS of 75% and 75%, respectively [28] . Regardless of HIV status, a US retrospective research for HIV-BL reported a 3-year PFS and OS rate of 64% and 70%, respectively [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the rst-line regimens used are R-CHOP-based regimens (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisolone) and DA-EPOCH-R [11,12] . HIV-BL, which accounts for 35% of NHL subtypes, is more prevalent in PLWH with a comparatively elevated CD4 cell count [13] . The incidence of BL has not decreased throughout the ART era, in contrast to other subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Though results vary depending on the used source, some studies show how HIV patients with lymphoma diagnosis have a lower OS than patients without HIV, with no impact on PFS. Moreover, in these patients, the disease tends to have more aggressive features at diagnosis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in a recent Spanish cohort of patients from the cART era, HIV-positive DLBCL patients had a worse prognosis with decreased overall survival at 5 years of 56% compared to 74% in HIV-negative patients [ 89 ]. A recent Australian study of HIV-positive lymphoma patients reported an excellent 2-year PFS of 77% and an OS of 81% using curative immuno-chemotherapy together with cART [ 90 ]. The frequency of HIV infection in a large cohort of DLBCL patients is 5.4% in US patients [ 23 ].…”
Section: Viral Infectionsmentioning
confidence: 99%